1989
DOI: 10.1148/radiology.172.1.2740512
|View full text |Cite
|
Sign up to set email alerts
|

Small, superficial esophageal carcinoma treated with high-dose-rate intracavitary irradiation only.

Abstract: Six patients with small, superficial carcinoma of the esophagus were treated with 18-24 Gy of high-dose-rate intracavitary irradiation only. All patients were examined with an endoscope within 1 month after therapy, and the tumor in all six had disappeared. However, erosion induced by high-dose-rate intracavitary irradiation was seen in five of the patients. Five of the patients have experienced no local recurrence; endoscopic biopsy showed local recurrence in the remaining patient 7 months after radiation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Furthermore, the beneficial effects of IBT after RT on the prognosis still remain unknown. [9][10][11][12][13][14][15][16] In regard to previous reports on the effects of IBT for T1, N0 tumor, Okawa et al . 9 showed that the LRC in patients treated with EBRT plus IBT was more favorable than that in the group receiving EBRT alone.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, the beneficial effects of IBT after RT on the prognosis still remain unknown. [9][10][11][12][13][14][15][16] In regard to previous reports on the effects of IBT for T1, N0 tumor, Okawa et al . 9 showed that the LRC in patients treated with EBRT plus IBT was more favorable than that in the group receiving EBRT alone.…”
Section: Discussionmentioning
confidence: 95%
“…19,20 Therefore, it is possible that CRT can yield improved tumor control in highrisk patients with SMEC. However, it has been reported that RT alone is a very effective treatment for T1, N0 tumor [9][10][11][12][13][14][15][16] and, in Japan, there will be a great demand for the treatment without an additive chemotherapy because the number of patients of advanced age has been rapidly increasing. In fact, 35% of patients in this study were 75 years old or over, and this trend is to be further expected in an aging society of Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This high complication rate apparently is related to the high fraction size of HDR-IBT. In fact, Hishikawa et al 13,14 used a fraction size of 6 Gy at 5 mm from the surface of a 10-mm applicator. Although we reduced the fraction size to 4 Gy in the current study, there were still two esophageal ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 han publicado no sólo un aumento del control local para los pacientes tratados con braquiterapia sino también un aumento de la supervivencia.…”
unclassified